Teaching Aptitude of Pre-service Teachers towards Inclusive Education Construction and Standardisation of IETAT - Mistry, H.S.; Panigrahi, S.C. (JOURNAL OF INDIAN EDUCATION, 2021)
Teaching aptitudes of pre-service teachers towards inclusive education of students with disabilities were examined. A 50-item test was constructed based on the literature review, experts’ judgement and pilot testing, and administered on the 552 pre-service teachers enroled in the first year of two-year Bachelor of Education program at thirteen teacher education institutions of Gujarat. The result of the study showed that the test found to have good reliability and validity. The participants had an average level of teaching aptitude towards inclusive education of students with disabilities. The paper concludes with the possible implications for teacher education institutions, stakeholders and policy makers.